A food‐based approach could improve dietary adequacy for 12–23‐month‐old Eastern Ugandan children. Issue 2 (3rd January 2022) - Kimere, Njeri C.; Nambooze, Joweria; Lim, Haeun; Bulungu, Andrea L.S.; Wellard, Kate; Ferguson, Elaine. L.
Abstract: Little is known about dietary adequacy, for young Ugandan children, or context‐specific food choices to improve it. This study estimated the percentage of breastfed 12–23‐month‐old rural Eastern Ugandan children ( n  = 114) at risk of inadequate intakes of 12 nutrients; and identified realistic food choices for improving it. In this cross‐sectional survey, dietary (weighed food records), anthropometric and socioeconomic data were collected. The percentages of children at risk of inadequate nutrient intakes were estimated, assuming 541 g/day of breast milk was consumed. The median nutrient densities of their complementary feeding diets were also compared with desired levels. Linear programming analyses were used to identify 'problem nutrients' (where requirements will be difficult to meet given dietary practices) and model food choices to improve dietary adequacy. Overall, 21.2% of children were stunted and 3.8% were wasted. A high percentage (>45%) of children were at risk of inadequate intakes, for nine of the 12 nutrients assessed, and dietary nutrient densities were below desired levels for seven of the 12 nutrients. Iron, calcium, thiamine and niacin were 'problem nutrients'. Through careful selection of foods, modelling indicates that population level dietary adequacy can be achieved for eight of the 12 nutrients modelled. These choices include cows' milk, legumes, green leafy vegetables, sweet potatoes and fruits. Overall results suggest these high percentages of children at risk of inadequate nutrient intakes can be reduced through behaviour change interventions, although additional interventions may be required to ensure population‐level dietary adequacy for iron, thiamine and niacin. Key messages: Dietary adequacy, for breastfed 12–23‐month‐old rural Eastern Ugandan children, is poor with over 45% of children at risk of inadequate intakes of nine micronutrients. Inadequate intakes of micronutrients likely contribute to growth faltering in this population where 21% of children are stunted but less than 4% are wasted. Dietary adequacy can be improved through careful selection of nutrient‐dense foods, including cows' milk, legumes, green leafy vegetables, sweet potatoes, and fruits. A food‐based approach alone, however, will not reduce the percentage of children at risk of inadequate intakes to low levels, for iron, thiamine and perhaps niacin, indicating alternative interventions are required.